Lumberjanes. Campfire songs - Andelfinger, Nicole; Williams, Brittney, 1989-; McGuire, Seanan; Costa, Mari; Prince, Liz; Watters, Shannon (Boom! Box, 2020)
Presents six adventures of five best friends at Miss Qiunzella Thiskwin Penniquiqul Thistle Crumpet's Camp for Hardcore Lady-Types.